IDENTIFIKASI DAN PENYEBARAN JENIS MANGROVE DI BAGIAN TIMUR PULAU MENIPO TAMAN WISATA ALAM PULAU MENIPO - Meylin Renny Pathibang; Diftan Meyduarti Tanea; Jeriels Matatula (Politeknik Pertanian Negeri Kupang, 2023)
A mangrove is a forest composed by various types of mangroves that live in areas where rivers and seas meet. This research was conducted to identify mangrove species in the eastern part of Menipo that use the 100% census method. The types of Mangroves found on Menipo Island in the eastern’s Nature park were 1. Rhizopora stylosa with 131 individual seedlings, 304 individual saplings, 290 individual trees, 2) Ceriops tagal with 122 individual saplings and 143 individual trees, 3) Rhizophora mucronate with 167 individual seedlings, 82 individual saplings and 190 individual trees, 4) Bruguiera parviflora with 79 individual saplings and 115 individual trees, and 5) Bruguiera cylindrical with 5 sapling stages of 3 individual trees. Key Words: Mangrove, Identification, Distribution, Menipo Island